ANALISA VISUAL ENTRY GATE DALAM RANGKA PENINGKATAN PELAYANAN LALU LINTAS PENERBANGAN DI BANDAR UDARA PATTIMURA AMBON - Andre Aziz Setyoutomo; Julfansyah Margolang; Meita Maharani Sukma (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The visual entry gate has an important role in flight efficiency in carrying out a visual approach. The visual entry gate serves as a reference for aircraft to make a visual approach through a certain point that has been determined so that ATC will find it easier to find out the position of the aircraft. The problem that is reviewed in this final project is regarding the imperfect visual entry gate related to some information that has an impact on the provision of air traffic services at Ambon Pattimura Airport. The analytical method used in this study is descriptive qualitative, namely data that describes the general conditions of using visual entry gates in providing air traffic services at Pattimura Airport, Ambon. Data collection methods used are observation, interviews, and literature study. This study concludes that visual entry gate improvements are needed for the efisiency and safe movement of aircraft at Ambon Pattimura Airport. The incomplete information on the visual entry gate has the potential to make air traffic feasibility less than optimal and also results in the visual entry gate not being able to be published into the AIP.